AB0836 THE INVESTIGATION OF BONE METABOLIC MARKERS ACCORDING TO THE FUNCTIONAL DISORDERS AMONG PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Kawano, Tetsuya; Kashiwagura, Takeshi; Aizawa, Toshiaki; Kobayashi, Moto; Urayama, Masakazu; Konishi, Natsuo; Sakuraba, Tsutomu; Itoh, Hiroki; Abe, Hidekazu; Suzuki, Norio; Kamo, Keiji; Aonuma, Hiroshi; et al.
Abstract : Background: Rheumatoid arthritis (RA) is one of the causes of secondary osteoporosis, and steroids are often used in combination, therefore osteoporosis is highly associated with RA. Furthermore, joint disorders due to RA cause various degrees of dysfunction and ADL declines. The Steinbrocker classification is often used as the degree of dysfunction. Immobilization progresses with the progress of dysfunction, possibly causing severe osteoporosis. Objectives: Of the 2238 cases in Akita Orthopedic Group omn Rheumatoid Arthrotis (AORA) registry 2017, 101 cases simultaneously measuring bone metabolism markers (TARCP-5b, NTX, urinary DPD, BAP, total P1NP) and pentosidine were involved. Methods: Patients were divided by Steinbrocker classification into class 1, 2 (group A 84 cases) and clss 3, 4 (group B 17 cases). we examined whether there is a difference in bone metabolism markers in each group according to Steinbrocker classification. Results: The average age in group B (75.9) was significantly higher than group A (66.9) (p = 0.01). DAS 28 ESR was significantly higher in group B (p < 0.01). There was no difference in eGFR representing renal function between the two groups. The urinary DPD (nM/mM Cr) and pentosidine (μg/ml) in group B was significantly higher than group A (p <0.01). No difference was observed between the two groups in other bone metabolism markers. Conclusion: Immobilization by long-term bed rest is known to enhance bone resorption. In 2002, Wakae reported DPD in urine showed a higher value in the group of not going out in femoral neck fracture cases. Based on the results of this study, urinary DPD showed a high value in RA group with high degree of dysfunction, which possibly reflected immobilization due to progress of functional disorder. Moreover, it is known that pentosidine will be higher in cases with high disease activity, severe osteoporosis will be occurred in the group with progressive functional disorder which is difficult to tight control. Disclosure of Interests: None declared